Spectrophotometric Determination of Gemifloxacin in Bulk and Pharmaceutical Formulation - Ganapathy, S.; Raju, G.V.H.; Sankar, D.G.; Y. Naidu, Pettla (Asian Journal of Chemistry, 2010)
A three simple, sensitive and reproducible visible spectrophotometric methods (methods A-C) are developed for the determination of gemifloxacin in pure and dosage forms. Method A is based on the formation of coloured species on treatment of reduced gemifloxacin with Folin- Ciocalteu reagent in presence of 4 % NaOH solution. Method B is based on the formation of coloured species on treatment of gemifloxacin with 3-methyl-2-benzo thiazolinone hydrazone and ferric chloride. Method C is based on the formation of coloured species on treatment of gemifloxacin with FeCl3 and 1,10-phenanthorline.